Hematopoietic cell transplantation in pediatric chronic myeloid leukemia - Gouveia, Roseane Vasconcelos; Michalowski, Mariana Bohns; Klinger, Paulo Henrique dos Santos; Domingues, Luciana dos Santos; Correa, Ana Carolina Ribeiro; Caleffi , Mariane Farherr; de Macedo, Antonio Vaz (JOURNAL OF BONE MARROW TRANSPLANTATION AND CELLULAR THERAPY, 2026)
Chronic myeloid leukemia (CML) is a clonal myeloproliferative disorder primarily linked to the BCR-ABL fusion gene, resulting from the Philadelphia chromosome translocation. While rare in pediatric populations, CML in children presents unique biological and clinical features, often diagnosed incidentally through leukocytosis. Symptoms may include fatigue, weight loss, and splenomegaly, with advanced cases exhibiting signs of bleeding and infections. The management of pediatric CML has evolved significantly with the introduction of tyrosine kinase inhibitors (TKIs), in which imatinib remains the first-line treatment despite potential long-term toxicities. Second-generation TKIs such as dasatinib and nilotinib are alternatives for treatment resistance. Asciminib, a third-generation inhibitor, shows promise for cases resistant to other TKIs, although pediatric data are still emerging. Allogeneic hematopoietic cell transplantation (HCT) is crucial for highrisk pediatric CML cases, particularly in the blastic phase or in instances of TKI resistance. The choice of conditioning regimens, whether myeloablative or reduced-intensity, is vital, with busulfan-based regimens preferred due to lower late effects. Post-transplant, the use of TKIs can be beneficial, with molecular monitoring guiding treatment decisions. Overall, individualization of therapy considering disease phase, molecular profile, and donor availability is essential for optimizing outcomes in pediatric CML management. Close follow-up strategies involving regular molecular assessments and tailored therapeutic approaches post-HCT are critical for improving patient survival rates and managing relapses.